A novel host restriction factor MRPS6 mediates the inhibition of PDCoV infection in HIEC-6 cells - Jiang, Yuhang; Zhang, Guoqing; Li, Letian; Chen, Jing; Hao, Pengfei; Gao, Zihan; Hao, Jiayi; Xu, Zhiqiang; Wang, Maopeng; Li, Chang; Jin, Ningyi (Frontiers in Immunology, 2024)
Porcine deltacoronavirus (PDCoV) is a zoonotic pathogen with a global distribution, capable of infecting both pigs and humans. To mitigate the risk of cross-species transmission and potential outbreaks, it is crucial to characterize novel antiviral genes, particularly those from human hosts. This research used HIEC-6 to investigate PDCoV infection. HIEC-6 cells were infected with PDCoV. Samples were collected 48 h post-infection for proteomic analysis. We discovered differential expression of MRPS6 gene at 48 h postinfection with PDCoV in HIEC-6 cells. The gene expression initially increased but then decreased. To further explore the role of MRPS6 in PDCoV infection, we conducted experiments involving the overexpression and knockdown of this gene in HIEC-6 and CaCO-2Caco2 cells, respectively. Our findings revealed that overexpression of MRPS6 significantly inhibited PDCoV infection in HIEC-6 cells, while knockdown of MRPS6 in CaCO-2Caco2 cells led to a significant increase in of virus titerPDCoV infection. Furthermore, we investigated the correlation between PDCoV infection titer and the level of PDCoV replication and assembly in HIEC-6 cells, as well as the expression of MRPS6. Subsequent investigations demonstrated that MRPS6 exerted an augmentative effect on the production transcription of IFN-β through upregulation of IRF-3 expressioninterferon pathway activation, consequently impeding the progression of PDCoV infection in cellular systems. In conclusion, this study utilized proteomic analysis to investigate the differential gene MRPS6protein expression in PDCoV-infected HIEC-6 cells, providing evidence for the first time that the MRPS6 gene plays a restrictive role in PDCoV virus infection. Our findings initially provide theInitial validation of the role of MRPS6 as an upstream component of IFN-β pathway, in the promotion of IFN-β transcriptionIRF3, IRF7, STAT1, STAT2 and IFN-β production of HIEC-6 via dual-activation from interferon pathwayvia the up-regulation of IRF-3 expression.